Engineering luminescent carbon dot emission through surface state functional group via heteroatom doping and unveiling the effect of solvents - Devi, Suman; Luwang, Meitram Niraj (Langmuir, 2025)
This work comprehends the synthesis of carbon dots from papaya leaves (PCD) using water, ethanolamine (EA), and dimethylformamide (DMF). Ethylenediamine (EDA) was used to introduce nitrogen doping. Water-based PCDs emit blue light, while those in EA and DMF emit red light due to increased oxidation. In EA or DMF with EDA, red emission quenches, and enhanced blue emission is observed, which infers reduced oxidation. This indicates that EDA shifted the emission back to the blue. These findings were confirmed by hypothetical mechanistic studies, Raman spectroscopy, and X-ray photoelectron spectroscopy (XPS). The Raman spectrum revealed defect-activated D and G bands; defects increase in pure solvents compared to water but decreases in mixed solvents such as EA + EDA and DMF + EDA. In XPS, C-O bonds were detected at a higher level in EA and DMF, whereas C-N bonds were observed at a higher level in EDA. TEM images showed that the synthesized PCDs ranged from 1 to 5 nm, with interplanar spacing values consistent with X-ray diffraction (XRD) analysis. PCDs synthesized from a sustainable carbon source exhibit tunable fluorescence from blue to red and vice versa based on solvents used during the engineering of surface state functional group. This makes them promising candidates for fluorescent security inks.